Gap Analysis of Graduates Competencies in Manufacturing Engineering Department with the Industry - Risky Ayu Febriani; Suseno Suseno; Jata Budiman; Agus Surjana Saefudin; Akil Priyamanggala Danadibrata (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
Bandung Polytechnic for Manufacturing (Polman Bandung) as one of the educational institutions that uses Production Based Education (PBE) in the teaching and learning process needs to prepare graduates who can compete in Industry that demands adequate creativity and skills. In order to ensure that graduates are the best and ready to enter the working and industry, the D3 Study Program - Precision Tool Manufacturing Technology (TPPP), which is under the Manufacturing Engineering Department, Polman Bandung, needs to carry out a fundamental transformation in its curriculum. To realize it, this Study Program carries out an Assessment Program for Curriculum Alignment that analyzing industry satisfaction from competencies of graduates. The competency consists of the core competency, hardskills competency, and softskill competency. The purpose of this study is to find out the gap between competency of students and industrial needs and analyzing industry satisfaction with the quality of academic services at Polman Bandung. The analytical method used was Importance Performance Analysis (IPA) method, this method is an analysis technique which is used to find out which competencies need to be increased. The sampling data was collected from graduates in the last 3 years, industries in which graduates of the last 3 years work, student in the last year, and lecturer. The measured competencies will be classified in 4 quadrants, quadrant 1 recommended to be improved, quadrant 2 is satisfying and its performance must be maintained, quadrant 3 low priority, and quadrant 4 overkill. Based on IPA analysis, the competency which need to be improved comes from quadrant 1 as known a high priority improvement. The results of this competency gap will be analyzed to improve education program by transforming its curriculum.